THE RELATIONSHIP AMONG SELF CONFIDENCE, LEARNING DISCIPLINE, AND USE OF LEARNING RESOURCES WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII OF MTsN YOGYAKARTA II - Syah Fathi Azzatia; Abdul Taram (Universitas Ahmad Dahlan, 2017)
Low of student mathematics learning outcomes are related to several factors. Self Confidence, learning discipline, and use of learning resources is some of the factors related to learning outcomes. This research aims to determine the presence or absence of a positive and significant relationship among confidence, learning discipline, and use of learning resources with mathematics learning outcomes in students class VIII of even Semester of Â MTsN Yogyakarta II in the academic year of 2015/2016. The population in this study was the girl students of grade VIII in MTsN Yogyakarta II in the academic year of 2015/2016, which was divided into 4 classes, namely VIII D, VIII E, VIII F, VIII G totaling 137 students. Samples were taken in class VIII E as research class sample and with random sampling technique to the class. Data was collected by questionnaire and test method. The research instrument were validity test, different power test, and reliability test. Test requirement analysis includes test of normality, linearity, and the independence. Analysis of the data for testing hypothesis using correlation and linear regression analysis. The results showed that there was a positive and significant relationship among self confidence, learning discipline, and use of learning resources with mathematics learning outcomes students of class VIII of even Semester in MTsN Yogyakarta II in the academic year of 2015/2016. It was showed by Fcount = Â Ftable = 2.9011 with R = 0.511998 and R2 = 0.2621 with , with SR = 30.7344 , SR = 18.5067% ,and SR = 50.75895% SE = , SE = and SE = 13.3060524 %.